Alteration of the N6-methyladenosine methylation landscape in a mouse model of polycystic ovary syndrome - Lingxiao Zou; Waixing Li; Dabao Xu; Shujuan Zhu; Bin Jiang (BMC, 2023)
Abstract Objective To explore the N6-methyladenosine (m6A) methylation abnormality of mRNAs and its potential roles in the mouse model of polycystic ovary syndrome (PCOS). Methods The mouse model of PCOS were induced by injecting dehydroepiandrosterone (DHEA), and confirmed by observing the morphological structures of ovarian follicles. Subsequently, m6A-tagged mRNAs were identified via m6A epitranscriptomic microarray and its potential functional pathways were predicted in KEGG database. The expression and modification levels of key mRNAs in the most enriched pathway were evaluated and compared using western blot and methylated RNA immunoprecipitation-quantitative PCR (MeRIP-qPCR). Results Compared with the control group, 415 hypermethylated and downregulated mRNAs, 8 hypomethylated and upregulated mRNAs, and 14 hypermethylated and upregulated mRNAs were identified in the PCOS group (Fold change ≥ 1.5). Those mRNAs were mainly involved in insulin signaling pathway, type II diabetes mellitus, Fc epsilon RI signaling pathway, inositol phosphate metabolism, and GnRH secretion. In insulin signaling pathway, the expression levels of phosphorylated protein kinase B (p-AKT) were decreased, whereas that of upstream phosphorylated phosphatidylinositol 3-kinase (p-PI3K) were increased in PCOS group. Moreover, skeletal muscle and kidney-enriched inositol polyphosphate 5-phosphatease (SKIP), one of PIP3 phosphatases, was verified to be overexpressed, and Skip mRNAs were hypermethylated in PCOS group. Conclusion The altered m6A modification of mRNAs might play a critical role in PCOS process. The PI3K/AKT pathway is inhibited in the mouse model of PCOS. Whether it is caused by the m6A modification of Skip mRNAs is worthy of further exploration.